Mechanisms and Therapeutic Potential of SGLT2 Inhibitors - Talarek, Konrad; Śliwa, Wiktoria; Szelc, Sylwia; Szuciak, Anna (Journal of Education, Health and Sport, 2026)
Introduction and Purpose. Epidemiological data indicate that the global prevalence of diabetes is projected to reach 784 million by 2045. This trend is closely associated with an increase in chronic kidney disease (CKD) and heart failure (HF), which remain the primary causes of mortality in this population. Sodium-glucose cotransporter 2 (SGLT2) inhibitors, or gliflozins, were originally developed as hypoglycemic agents but have demonstrated significant pleiotropic benefits. The purpose of this study is to analyze the multidimensional mechanisms of SGLT2 inhibitors and evaluate their clinical impact on type 2 diabetes, heart failure, and renal protection. Brief Description of the State of Knowledge. Gliflozins function through an insulin-independent mechanism by blocking glucose reabsorption in the proximal renal tubules, leading to glycosuria. This process effectively lowers HbA1c levels without inducing hypoglycemia. Beyond glycemic control, SGLT2 inhibitors activate tubuloglomerular feedback, leading to afferent arteriolar vasoconstriction and a reduction in intraglomerular pressure. These drugs provide significant cardioprotection by reducing cardiac preload and afterload and improving myocardial energy efficiency through ketone body utilization. Clinical trials confirmed that gliflozins reduce hospitalizations for HF. Furthermore, they contribute to weight loss and blood pressure reduction. While generally safe, they are associated with risks of urogenital infections and rare complications such as euglycemic ketoacidosis. Summary. SGLT2 inhibitors represent a breakthrough interdisciplinary therapy. Their potential efficacy in reducing cardiovascular mortality and renal failure progression is observed in both diabetic and non-diabetic patients. Given their organ-protective properties, gliflozins have become a cornerstone in modern diabetology, cardiology, and nephrology.